Os conhecimentos tradicionais nas práticas de manejo de pirarucu (arapaima gigas) no Médio Solimões, Amazonas - Gonçalves, Ana Cláudia Torres (2018)
This research analyzed the epistemological bases of pirarucu management, seeking to identify the traditional knowledge present, and investigating the extent to which these knowledge were scientifically recognized and subsidized the normative and management practices in force. In this sense, the course involved the description of traditional knowledge in the pirarucu fishery - in which the learning process in the fishery was evidenced, discussing the knowledge, practices and skills of a pirarucu fisherman. Followed by the description of the management practices, using as reference the management practices observed in the fishery agreement of the Paraná do Jacaré lakes complex; Finally, the social representations of pirarucu management, based on the analysis of norms and scientific publications, verifying the occurrence or not of references to the traditional knowledge, and also evidencing the perceptions of fishermen, technicians and environmental analysts on the management. The research is based on a qualitative approach, using methodological procedures such as bibliographic research; documentary research; interviews; and case study with participant observation, which subsidized the description and analysis of the pirarucu management stages that includes: mobilization and social organization, zoning of the fishing territory; the protection of the area; the survey of the pirarucu stock; fishing; monitoring production; marketing and evaluation of activities.